Hypertension and Type 2 Diabetes: Prevalence and Risk Factors among Adults, Suggested Nursing Protocol - Nagwa Mohamed, Ahmed Mohamed (Pakistan Journal of Medical & Health Sciences, 2022)
In addition to clinical problems in both economically developed nations as well as emerging countries, hypertension and type 2 diabetes pose challenges to human safety in general. The spread of factors leading to hypertension and type 2 diabetes among Saudi citizens has caused epidemic proportions due to the richness of the quality of life. The research aims to Assessing the level of hypertension and type 2 diabetes in Saudi adults and to establish a suggested nursing procedure for the early diagnosis of hypertension and type 2 diabetes. Descriptive and association analysis methodology has been used. Where 120 adults engaged in the research at Tabuk University in Saudi Arabia from September 2018 to March 2019. 10% of participants were hyperglycemic and more than 10% were hypertensive, and the major risk factors were sedentary behaviors for more than 3 hours a day and carbonated drinks/fruit juice. This research indicates that type 2 diabetes and hypertension will impact people with significant health problems in the future. The main effort to encourage healthier nutrition, active living, regular fitness and a healthy lifestyle is also a health issue. Keywords: Prevalence, Risk Factors; Hypertension; Type 2 diabetes; Suggested Nursing Protocol.